Olfactory Outcomes With Dupilumab in Chronic Rhinosinusitis With Nasal Polyps - Mullol, Joaquim; Bachert, Claus; Amin, Nikhil; Desrosiers, Martin; Hellings, Peter W; Han, Joseph K; Jankowski, Roger; Vodicka, Jan; Gevaert, Philippe; Daizadeh, Nadia; Khan, Asif H; Kamat, Siddhesh; et al. (The journal of allergy and clinical immunology. In practice, 2022)
BACKGROUND: Loss of smell (LoS) is one of the most troublesome and difficult-to-treat symptoms of severe chronic rhinosinusitis with nasal polyps (CRSwNP). OBJECTIVE: To assess the impact of dupilumab on sense of smell in severe CRSwNP. METHODS: In the randomized SINUS-24 and SINUS-52 studies, adults with severe CRSwNP received dupilumab 300 mg subcutaneously or matching placebo every 2 weeks for 24 or 52 weeks, respectively. Smell was assessed using daily patient-reported LoS score (0-3) and University of Pennsylvania Smell Identification Test (UPSIT; 0-40). Data from the 2 studies were pooled through week 24. Relationships between patient phenotypes and smell outcomes were also assessed. RESULTS: We randomized 724 patients (286 placebo, 438 dupilumab); mean CRSwNP duration was 11 years; 63% had prior sinonasal surgery. Mean baseline LoS was 2.74. Dupilumab produced rapid improvement in LoS, evident by day 3, which improved progressively throughout the study periods (least squares mean difference vs placebo -0.07 [95% CI -0.12 to -0.02]; nominal P < .05 at day 3, and -1.04 [-1.17 to -0.91]; P < .0001 at week 24). Dupilumab improved mean UPSIT by 10.54 (least squares mean difference vs placebo 10.57 [9.40-11.74]; P < .0001) at week 24 from baseline (score 13.90). Improvements were unaffected by CRSwNP duration, prior sinonasal surgery, or comorbid asthma and/or nonsteroidal anti-inflammatory drug-exacerbated respiratory disease. Baseline olfaction scores correlated with all measured local and systemic type 2 inflammatory markers except serum total immunoglobulin E. CONCLUSIONS: Dupilumab produced rapid and sustained improvement in sense of smell, alleviating a cardinal symptom of severe CRSwNP.
Keywords: Smell; nosní polypy; sinusitida; Humans; Quality of Life; Chronic Disease; dospělí; výsledek terapie; Sense of smell; lidé; humanizované monoklonální protilátky; rýma; kvalita života; Nasal Polyps; Dupilumab; Adult; Type 2 inflammation; čich; Antibodies, Monoclonal, Humanized; chronická nemoc; Treatment Outcome; Sinusitis; Anosmia; Rhinitis; Chronic rhinosinusitis with nasal polyps